Draft Five Year Plan 1978-83 Sectoral Programmes Government of Gujarat - Planning Commission (Planning Commission, 1978)
The soil and climate of Gujarat determine the cropping pattern of the State. Extreme variability in the distribution of rainfall is a peculiarity of the State. Geographically the basic complex of the State varies from region to region. Soils in southern region are deep black (soils of basaltic origin), central and northern parts of the State have old alluvium and the Saurashtra region has medium black soils of basaltic origin, while all along the coasts line aluminium is found. The variations in rainfall and soil types can be largely attributed to geographical situation of the state. The State is located in the fringe of the area of South West monsoon. The rainfall therefore is confined to 3 to 4 months only from June to September with practically no precipitation in winter months. The annual normal rainfall varies from 349.4 mm in Lakhpat taluka of Kachchh district to 2409.8 mm in Dharampur taluka of Valsad district.
Government of Gujarat, General Administration Department (Planning)